The challenges in lifetime prediction of oxodegradable polyolefin and biodegradable polymer films. (November 2017) - Nikolić, Melissa A.L.; Gauthier, Emilie; Colwell, John M.; Halley, Peter; Bottle, Steven E.; Laycock, Bronwyn; Truss, Rowan
Abstract: The service lifetime of polymer films is controlled by the chemical reactions leading to chain scission and the mediating environmental factors. For application as agricultural cropping film, controlled accelerated degradation is required. For a photo-sensitive linear low density polyethylene (LLDPE) + 1% nano-titania (as the anatase/rutile mixed phase P25), the environmental factors are not only UV dose and temperature but also soil parameters such as moisture and organic material content. This provides a challenge in predicting the useful lifetime from laboratory accelerated ageing studies. To enhance degradation when the (LLDPE + 1% P25) is buried, UV-C pre-irradiation has been shown to accelerate strength loss but the rate of embrittlement is not sufficient for the application as crop propagation film. Biodegradable poly(butylene adipate- co -terephthalate) or PBAT has a higher rate of degradation when buried outdoors in soil than when buried under laboratory conditions: The elongation at break fell from 900% to 70% in one month in the field while similar changes required 6 months in the laboratory. The small changes in M n ¯ for embrittlement in the field suggests that the loss of mechanical properties was not linked to bulk property changes but rather to surface morphology (cracks and holes) as seen by SEM. This suggests that even in thin films, enzyme-mediated hydrolysis of PBAT is surface controlled. DNA analysis of the soil around the buried films after 35 days ageing outdoors showed fungi play a more dominant role in PBAT biodegradation compared to bacteria. UV degradation of PBAT film is controlled by the photochemistry of the terephthalate moiety in the polymer and the development of fluorescence is a useful indicator of the extent of photo-degradation.